In situ defect quantification and phase identification during flash sintering using Raman spectroscopy. Issue 8 (16th April 2021) - Murray, Shannon E.; Lv, Guangxin; Sulekar, Soumitra S.; Cahill, David G.; Shoemaker, Daniel P.
Abstract: Flash sintering has been established as a method to rapidly densify or induce phase transformation in materials by applying an electric field. Understanding rapid transformations is challenging in a laboratory setting, where phase and defect populations may change with sub‐second time scales. In this work, we apply in situ Raman spectroscopy to investigate defect complexes and phase transformations during flash sintering. We demonstrate that the oxygen vacancy complexes in Ce0.85 Gd0.15 O1.925 and the evolving phases in a SrCO3 + V2 O5 reaction can be probed with acquisition times sufficient to monitor stage II of flash sintering. We establish how thermal effects can be separated from effects of the electric field and determine the resolution of the defect concentration. The fast characterization we demonstrate here can be combined with well‐developed models of thermal and phase evolution to elucidate the mechanism of densification during flash sintering.